Determinants of financial vulnerability mediated by financial management practices among civil servants in Peninsular Malaysia - Lee, May Poh (2020)
The affection of the global financial crisis, rising debt problem, and bankruptcy among civil servants in Malaysia are perturbing. To date, there is no previous study on the factors of financial literacy, financial attitudes, and self-efficacy in examining financial vulnerability. Therefore, this study aims to determine the relationships between financial vulnerability and its predictors (financial literacy, financial attitude, and self-efficacy) and mediated by financial management practices among the civil servants in Peninsular Malaysia. A quantitative methodology using a self-administered questionnaire as a tool for collecting data involved a total of 590 civil servants in Peninsular Malaysia selected through a multi-stage random sampling. The results showed that there were positive significant relationships between financial attitude (r= .338, p= .000), self-efficacy (r= .407, p= .000), excepted for financial literacy (r= .036, p= .409) with the financial vulnerability. Also, financial management practices followed by self-efficacy determinant of financial vulnerability. In testing the mediation effect, the indirect mediation effect of financial management practices existed and significant in the relationships between financial literacy (B= .246, p= .000), financial attitude (B= .246, p= .000) and self-efficacy (B= .324, p= .000) with financial vulnerability. A better understanding of financial vulnerability will increase the awareness of all civil servants in planning their savings, expenses as well as consumption and the research results are able to provide practical implication to business owners as well as the managerial level to their organisational planning and thus enhance the motivation as well as the practices of the working class leading to their achievement for better performance.